Kristapurāṇa: Translating the Name of God in Early Modern Goa - Alexander Henn (South Asia Multidisciplinary Academic Journal)
In the 16th and 17th centuries, Jesuit missionaries began to translate Christian doctrine and mythology into Indian languages. Most critical became the question how the very name(s) of God and gods can be translated. Artfully composed texts known as Christian Purāṇas borrowed from the religious terminology and literary styles of Indian devotional literature and are praised today for mediating between the cultures of Christians and Hindus (the latter called ‘gentiles’ in the contemporary sources). At the same time, the Portuguese-Catholic regime in India launched a ruthless iconoclastic campaign against the culture of the Indian gentiles, destroying their temples and images and denigrating their allegedly ‘false gods.’ Against this background, the article addresses the questions of what the relation was between translation and violence; how hermeneutics and destruction coexisted; and how the idea that the translations facilitated the modern emergence of religious pluralism is to be qualified.